2018
DOI: 10.14744/hnhj.2018.72677
|View full text |Cite
|
Sign up to set email alerts
|

Preoxygenation in the elderly: Comparison of three minutes and four deep breath tecniques

Abstract: Preoxygenation with 100% O 2 before anesthesia induction is a standard procedure in anesthesia practice. With preoxygenation, alveolar washout of air mixture in functional residual volume provides higher alveolar oxygen concentration up to 100% which leads to increased alveolar oxygen reserve, so during apnea, time to desaturation levels is delayed. We studied two different preoxgenation methods in elderly patients and compared four deep breath and 3-min techniques to decide which one is more efficient in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…T he term preoxygenation refers to the procedure of the alveolar exchange of the mixture of air inside the functional residual capacity (FRC) that contains nitrogen and water vapor with 100% oxygen (O 2 ). 1 Performing preoxygenation with high-fraction O 2 before anesthesia induction and endotracheal intubation (ETI), increases the O 2 reserve in the lungs, and it is a method that has been used and accepted for years because it delays the time of apnea-related desaturation development. 2 While preoxygenation can be performed using different methods, the most frequently utilized method is to inspire 100% O 2 for 2-10 minutes (min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T he term preoxygenation refers to the procedure of the alveolar exchange of the mixture of air inside the functional residual capacity (FRC) that contains nitrogen and water vapor with 100% oxygen (O 2 ). 1 Performing preoxygenation with high-fraction O 2 before anesthesia induction and endotracheal intubation (ETI), increases the O 2 reserve in the lungs, and it is a method that has been used and accepted for years because it delays the time of apnea-related desaturation development. 2 While preoxygenation can be performed using different methods, the most frequently utilized method is to inspire 100% O 2 for 2-10 minutes (min).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In addition to this, other recommended methods include the 4 deep breaths/30 seconds method that provides equivalent oxygenation to deep inspiration and deep expiration, providing the inflation of atelectatic areas in the basal lungs to increase FRC. 1 The efficiency of preoxygenation is determined based on the time from the onset of apnea to a certain lower limit of peripheral oxygen saturation (SpO 2 ). 6 Although it has been reported that SpO 2 levels should be >93% to obtain sufficient preoxygenation in emergencies, this practice might not show the adequacy of preoxygenation.…”
Section: Discussionmentioning
confidence: 99%